Molecular epidemiology of tuberculosis in the Czech Republic, 2004 - analysis of M. tuberculosis complex isolates originating from the city of Prague, South Moravia and the Moravian-Silesian region - Prodinger, Wolfgang M; Polanecký, Vladimír; Kozáková, Bohumila; Müllerová, Maria; Mezenský, Lev; Kaustová, Jarmila; Lechleitner, Carolin; Kubín, Milan (Central European Journal of Public Health, 2006)
Objectives: To compare M. tuberculosis complex genotypes from representative regions of the Czech Republic in order to estimate changes in strain prevalence and in the extent of imported drug-resistant tuberculosis. Methods: Primary M. tuberculosis complex isolates (n = 155) and follow-up isolates (n = 15) from 155 patients from the first half of 2004 (98 from Prague, 37 from South Moravia and 35 from the Moravian-Silesian region) were genotyped by IS6110-RFLP, spoligotyping, and partly by VNTR-genotyping. Results: Based on IS6110-RFLP, 110 of 155 (71%) primary isolates were unique. Forty-five isolates (29 %) were found in 15 clusters comprising two to six patients and all but one cluster were also discriminated by MIRU-VNTR-genotyping. Four clusters comprised patients from different regions, and six were ongoing for several years. An indication of MDR-strain transmission was found in one instance. All four Beijing-type isolates with any resistance were associated with immigration from Eastern Europe. Conclusions: The molecular epidemiological data of this period-prevalence, population based study and its comparison to earlier investigations point to a low extent of clustering between M. tuberculosis complex isolates in representative regions of the Czech Republic. Few clusters extending geographically and/or over several years were identified, providing a means for an in-depth analysis of risk factors of transmission. Beijing genotype isolates were shown to increase in prevalence to reach 6.5%. Drug resistant isolates of this genotype were associated with immigration of from Eastern Europe, although direct transmission of a resistant isolate was probable only in one of eleven cases.
Keywords: genotyp; Czech Republic; léková rezistence; DNA Fingerprinting; DNA fingerprinting; Tuberculosis; Drug Resistance; Česká republika; Molecular Epidemiology; Genotype; Humans; lidé; tuberkulóza; molekulární epidemiologie